RUNNING DICTATION TECHNIQUE AND LEARNING MOTIVATION: THEIR EFFECTS ON STUDENTS’ LISTENING COMPREHENSION ACHIEVEMENT - Merie Agustiani; Henny Yulia (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2018)
Abstract: Listening is considered as a basis of English skills. Unfortunately, students mostly have problems on word recognitions that make them have undeveloped vocabularies that automatically affect their listening comprehension. Running dictation was believed as a motivational teaching technique that can minimize these problems.  This study was aimed at investigating the effects of running dictation toward students’ listening comprehension achievement viewed from their learning motivation. This experimental study applied a 2 x 2 factorial design. Fifty students of English Education Study Program were chosen randomly on the basis of their learning motivation and assigned equally into two groups. The result showed that running dictation successfully improved students’ listening comprehension achievement (?<0.000); there were also significant difference of achievement between experimental and control group (?<0.000). Meanwhile, the ANOVA result showed that there was no interaction effect between techniques used and learning motivation on their listening comprehension achievement (?=0.867). Keywords: listening comprehension achievement, learning motivation, running dictation technique